Developing and validating a scale to measure perceived barriers to prosthodontics treatments among partially edentulous patients - Sharka, Rayan; Alghamdi, Majd; Dustakir, Eman; Alghamdi, Mansour (Frontiers in Oral Health, 2025)
BackgroundPeople experiencing tooth loss need dental prostheses to preserve the integrity of their oral structures and replace the missing teeth. Patient-related outcome measures (PROMs) for perceived barriers to prosthodontics treatment are scarce in the literature.AimsThe aim of this study was to develop a comprehensive scale to identify and measure barriers to prosthodontic treatment as perceived by partially edentulous patients.MethodsThis cross-sectional study was conducted among N = 334 partially edentulous adults who seeking prosthodontic treatment. Data collection was carried out in February to September 2024. Exploratory factor analysis was utilized to elucidate the latent factor structure. A six-factor model was validated through confirmatory factor analysis. Reliability was evaluated using Cronbach's alpha. The convergent and discriminant validity of the final scale were assessed.ResultsEFA produced a 21-item scale grouped into six factors that explain 75.78% of the total variance with eigenvalues >1. All items showed acceptable reliability, ranging from 0.807 to 0.935. The first factor pertained to financial constraints; the second factor was concerning lack of knowledge and awareness; the third factor was related to anxiety and fear; the fourth factor related to negative past dental experiences; the fifth factor included issues related to limited accessibility to dental services; and the last factor was concerning insufficient dental guidance. The CFA results indicate an acceptable model fit, with standardized factor loadings spanning from 0.54 to 0.99. The model factors’ convergent and discriminant validity were confirmed.ConclusionThis study enhances the understanding of barriers to prosthodontic treatment in a Saudi Arabian teaching dental hospital. It introduces a novel scale for further data collection, aiding policymakers and stakeholders in addressing these barriers and improving public oral health. Future studies should validate this scale and explore its applicability in various contexts and populations.